An Innovative Design to Improve Systematic Odometry Error in Nonholonomic Wheeled Mobile Robots - Murelitharan, Muniandy; Kanesan , Muthusamy
A major drawback with the popular differential drive wheeled mobile robot (WMR) when autonomously navigating on smooth indoor surfaces is its inability to continuously maintain straight-line trajectories. The inherent weakness of its kinematic design leads to this severe dead reckoning error that inevitably accumulates over the distance traveled. The mobile robot then depends on high resolution wheel encoders and rapid feedback control data processing capability that must continuously struggle to minimize this unproductive systematic odometry error. This paper proposes an innovative and robust drive train mechanical design called dual planetary drive (DPD) that will both drive a non-holonomic wheeled robot in straight lines effectively and more importantly, minimize systematic odometry error without the need for complex electronic feedback control systems. (Abstract by authors)